Feasibility analysis of insertion of Coconut Fiber in Soil-Cement (Research, Society and Development, 2022)
Over the years, civil engineering has evolved in terms of construction techniques and practical materials used in order to facilitate and cheapen the work. The environmental impact, when it began to be questioned, generated many criticisms of the civil construction sector, due to the waste of materials and difficulty in their disposal. The soil-cement brick came as a sustainable alternative for the environment, as it is considered ecologically correct. Thus, this study aims to produce low-cost bricks, using in its composition coconut fibers and soil from the Teófilo Otoni region, in order to discuss and evaluate the influence of these compounds on the material's properties and to study its economic and environmental viability. In the methodology of this work, the confection of the soil-cement brick with the addition of coconut fibers was carried out. Bricks with and without fiber were made in order to carry out laboratory tests of compression, in order to discuss the influence of fiber on the brick. Regarding compressive strength, the insertion of fibers allowed a significant gain, and bricks with fiber presented about 4.5 times more resistance than those without fiber. Therefore, it is concluded that the manufactured bricks meet the desired expectations, allowing the production of a material that fits the standard of concerns with the environment, feasibility of a form of use and increased compressive strength.